Feed evaluation - Osuji, P.O.; Nsahlai, I.V.; Khalili, H. (International Livestock Centre for Africa, 1993)
This manual has been produced to standardise some analytical procedures at ILCA and among those NARS scientists who may be interested in the aspects of feed evaluation which the manual attempts to address. The first part of the manual is on determination of voluntary intake, digestion and retention coefficients. It lists feed-intake measurement and collection of faeces and urine and presents procedures on preparing samples for chemical analysis. The second part examines special methods for measuring digestibility. This includes the indicator method, the nylon-bag technique, the nylon-bag procedure, handling nylon-bag data, and the Menke in vitro gas-production technique. The third part summarises the kinetics of digestion and of passage. Flow rates, rumen-evacuation technique, the use of markers to estimate passage rates, and continuous dosing with chromium-mordanted straw are discussed in this part. The fourth part is on the estimation of microbial protein supply using total urine excretion of purine derivatives. This includes sample preparation and mathematical procedures